Executive Compensation, Executive Character, Tax Avoidance: Does Independent Commissioner Matter? - Arista, Paula; Firmansyah, Amrie; Michelle, Michelle; Trisnawati, Estralita (Educoretax, 2024)
This study looks at the impact of executive compensation and character on tax avoidance. This study also looks at the moderating influence of the proportion of independent commissioners in this connection. This study uses secondary data from financial statements from consumer products businesses listed on the Indonesia Stock Exchange between 2017 and 2021, retrieved from www.idx.co.id. The overall sample size for this study was 85 observations, as determined via purposive sampling. Multiple linear regression was used to evaluate panel data. This research concludes that executive compensation is positively related to tax avoidance, while executive character does not affect tax avoidance. Furthermore, the proportion of independent commissioners succeeded in reducing the positive influence of executive compensation on tax avoidance, while the role of independent commissioners did not have a role in reducing the positive influence of executive character on tax avoidance. This research is expected to be a means for the Indonesian Tax Authority to create policies for profiling company compensation characteristics for executives as an initial indicator of tax avoidance activities carried out by companies.